F36. Imaging fascicle traffic in peripheral nerve using fast neural EIT. (May 2018) - Aristovich, Kirill; Donega, Matteo; Avery, James; Chew, Daniel; Holder, David
Abstract : Introduction: Fast neural Electrical Impedance Tomography (EIT) is a promising technique which can potentially be used for imaging neural activity over milliseconds with unprecedented spatial resolution without penetrating nervous tissue. Here we present the first cross-sectional images of fascicular neural activity measured during compound action potentials acquired in rat sciatic nerve in in vivo experiments. Methods: EIT was collected with a cylindrical cuff electrode wrapped around the sciatic nerve in the thigh in 4 adult Sprague-Dawley rats anaesthetized with Isoflurane nerve made of silicone rubber. 16 electrodes were placed around the circumference, each 2 × 0.1 mm, made of laser-cut stainless steel foil which was then platinised. Distal fibular and tibial branches were electrically stimulated with square pulses with 0.2 ms duration, 1 mA amplitude, and 200 ms inter–stimulus interval. EIT data was acquired during consecutive injection of alternating current, with amplitude 5–75 μ A and frequency 3–15 kHz, through a pair of electrodes at a time with simultaneous voltage recordings on the remaining electrodes. 16 independent current injections with 50 pulses per injection were recorded, resulting in 160 s image acquisition time. Acquired data was demodulated with 4 kHz bandwidth, averaged, and reconstructed with > 0.5 ms temporal resolution. 1M-element 3D forward mesh, and 20k-element inverse mesh was used for reconstruction; 0-th order Tikhonov regularisation with coefficient of variance correction was employed. Results were displayed as a Z-score with respect to the inter-stimulus noise. Results: Reproducible time-series images were reconstructed in each experiment, showing neural activity onset in ∼ 0.3–0.6 ms, after stimulus, peak at 0.6–1.5 ms, and subsequent decay at 1–2 ms. Images were obtained following electrical stimulation of the tibial or peroneal branches distally. Spatially distinguishable activity with centre-to-centre separation distance of 0.57 ± 0.04 mm (mean ± S.E.) was obtained in N = 24 experiments in n = 3 rats. EIT were much superior to those collected by Inverse Source Analysis (ISA) performed on CAPs recorded simultaneously to the EIT. Images were cross-validated with co-registered histological images. Comparison showed the position mismatch was 0.1 mm ± 0.03 mm between EIT and histology, and 0.14 mm ± 0.06 mm between EIT and inverse source imaging. Conclusion: Nerve fascicular traffic can be successfully imaged using EIT. This offers a potential means to identify the function of fascicles in autonomic nerve in vivo and so avoid off-target effect by selective stimulation. This could yield significant benefits in vagal nerve stimulation in epilepsy, where hoarseness is a limiting factor, and in the new field of Electroceutical treatment of disease by electrical stimulation of autonomic nerve.